Trends and risk factors for syphilis infection in Piedmont Region, Italy, 2002-2008 (Italian Journal of Public Health, 2011)
Background: This work aims to analyze trends of syphilis infections in the Piedmont Region (Italy) between2002 and 2008, and to evaluate risk factors for infection.Methods: Syphilis trends were described according to socio-demographic characteristics, sexual behavior,condom use, number of partners and HIV infection. Independent risk factors for syphilis among men havingsex with men (MSM), men having sex with women (MSW), and women were identified through logisticregression comparing cases with 12,773 negative patients.Results: Between 2002 and 2008, 1,046 cases of syphilis were diagnosed, with peaks in 2004 and 2007. Therisk of a syphilis diagnosis was independently associated with being older than 24, having a low educationlevel, homosexual behavior, HIV self-reported infection (for MSM and MSW), number of partners (for MSWand women) and non- consistent condom use (for women).Conclusions: Recent outbreaks suggest that the attention to syphilis can’t be lowered. Screening, treatmentof cases and notification of partners should be reinforced and integrated with sexual health education andcounselling in high-risk environments. Surveillance data must be continuously collected.
Keywords: syphilis; surveillance; trends; epidemic; HIV; risk factors